2022
DOI: 10.1155/2022/4355386
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Regulatory T Cells in Non-Small-Cell Lung Cancer: Current Advances and Future Perspectives

Abstract: Non-small-cell lung cancer (NSCLC) is one of the most threatening malignant tumors to human health, with the overall 5-year survival rate being less than 30%. Regulatory T cells (Tregs), a functional subset of T cells, maintain immunologic immunological self-tolerance and homeostasis. Accumulating evidence has uncovered their implicated roles in various cancers in recent years. In NSCLC, they are associated with staging, therapeutic efficacy, and prognosis by infiltrating in tissues and thereby attenuating imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 105 publications
0
20
0
Order By: Relevance
“…Besides TEX, other immunosuppressive characteristics are also essential to determine the degree of malignancy of TME, which influences immuno- and chemotherapeutic responses. Studies have shown that Treg, MDSC, and TAM extensively infiltrate advanced NSCLC ( Liang et al, 2022 ). In this study, CuRGcluster C, geneCluster B, and high-CuRGscore subtypes were significantly enriched in infiltrating Treg, MDSC, and TAM.…”
Section: Discussionmentioning
confidence: 99%
“…Besides TEX, other immunosuppressive characteristics are also essential to determine the degree of malignancy of TME, which influences immuno- and chemotherapeutic responses. Studies have shown that Treg, MDSC, and TAM extensively infiltrate advanced NSCLC ( Liang et al, 2022 ). In this study, CuRGcluster C, geneCluster B, and high-CuRGscore subtypes were significantly enriched in infiltrating Treg, MDSC, and TAM.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor associated-Tregs are present in multiple tissues of patients with LUAD, including tumors, metastatic lymph nodes, and the peripheral blood, playing a fundamental role in creating an immunosuppressive microenvironment in LUAD [37]. Tumor-resident Tregs may originate from peripheral Treg recruitment, local differentiation from naive T cells, the conversion of conventional T cells, or tissue Treg expansion [38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they can also be divided into cytotoxic T lymphocytes (CTLs), helper T lymphocytes (Th lymphocytes), and Tregs according to their function. [64][65][66] Overall, T lymphocyte classification is highly heterogeneous, and T lymphocyte infiltration plays a significant role in osteosarcoma immunotherapy. Fig.…”
Section: The Immune Microenvironment Of Osteosarcomamentioning
confidence: 99%